The effects of teacher support, feedback, and enthusiasm on middle school students' school belonging and self-efficacy - Xue, Yingying; Park, Kyung Hee; Wang, Fudan (International Journal of Innovative Research and Scientific Studies, 2025)
School serves as the primary context for adolescent development and is a crucial platform for socialization and identity formation. Adolescents have specific developmental needs, including seeking peer socialization, a sense of school belonging, and a positive self-perception. Within this context, teachers—who interact most directly with students—play an irreplaceable role in guiding and advancing students' socialization and identity formation. This study investigates the impact of teacher behaviors on students' sense of school belonging and self-efficacy within East Asian educational contexts. Using structural equation modeling, we analyze a subset of 1,391 Chinese middle-school students drawn from the PISA survey. Results indicate that teacher behaviors are essential for fostering students' development and growth. Specifically, teacher support for learning and assistance, feedback delivered in a readily understandable way, and teacher enthusiasm were identified as important promoters of students' school belonging. However, regarding perceived teacher support, the findings suggest potentially conflicting effects on belonging: the observed negative effect indicates that when perceived support fails to enhance belonging, it may paradoxically undermine students' confidence in their own competence. Taken together, these findings suggest that the external educational context of the school and students' subjective experiences interact to predict achievement-related outcomes.